CONDITIONS OF SKIN AND INTESTINE MICROBIOTES IN PATIENTS WITH PSORIASIS - Ya.O. Yemchenko; K.E. Ishcheikin; I.P. Kaidashev; G.Yu. Morokhovets (Проблеми екології та медицини)
Psoriasis is a chronic recurrent skin disease that affects about 2% of the world's population. Despite the fact that psoriasis is one of the most common immune-mediated inflammatory skin diseases, its exact driving factor remains unclear. In recent years, numerous scientific studies have detected significant dysbacteriosis of the skin and intestines in patients with psoriasis. Recent advances have highlighted the crucial role of microbiota in the pathophysiology of chronic inflammatory diseases as well as its impact on the efficacy of therapeutic agents. This literature review examines the microbiota of the skin and intestines and their role in the pathogenesis of psoriasis. In psoriasis-affected skin, a significant decrease in alpha-beta diversity of the microbiome was observed. Changes in the intestinal microbiome in psoriasis are similar to those observed in patients with inflammatory bowel disease. Changes in the microbiome associated with psoriasis can induce an inflammatory response by activating the cytokines IL-23, IL-17 and IL-22, as well as modulating gamma-interferon and inhibiting the production of T-regulatory cells. This leads to the uncontrolled growth of keratinocytes. Interactions between the microbiota and the immune system are important for establishing and maintaining host homeostasis. Modification of the composition of the microbiota can lead to a shift in the activation of the immune system and eventually to the development of inflammatory diseases. Disorders in the regulation of skin microbiota may become a new therapeutic target in patients with psoriasis, and the restoration of symbiosis may increase the effectiveness of existing treatments. Thus, the human microbiota plays a key role in various aspects of the disease, from its pathogenesis to response to treatment.